Use of digital e-learning technologies through the application of the SAM instructional design model in online medical education - Dan Alexandru SZABO (Editura Universităţii din Oradea, 2022)
Several instructional design behaviors are carried out by department operatives in higher teaching who lack formal learning theories and instructional science training. Teachers primarily use multimedia to deliver lectures in the form of power-point presentations. Even though there is a wealth of literature on using the program correctly, there are still some instances where the output is subpar. The application of digital technology in medical education is now regarded as a critical component of learning resources. The SAM method is defined as approximating an appropriate attention model successively. The first stage, evaluation, is divided into four sections: analysis, objectives, goals, and results. Design components are interaction, equivalence, technological options, appearance, and quality. The final stage is development, in which the objects and processes of design composition, development, and improvement are integrated.